2017
DOI: 10.3390/ijms18102027
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-Phosphate Signaling and Its Pharmacological Modulation in Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Allogeneic haemopoietic stem cell transplantation (HSCT) is increasingly used to treat haematological malignant diseases via the graft-versus-leukaemia (GvL) or graft-versus-tumour effects. Although improvements in infectious disease prophylaxis, immunosuppressive treatments, supportive care, and molecular based tissue typing have contributed to enhanced outcomes, acute graft-versus-host disease and other transplant related complications still contribute to high mortality and significantly limit the more wides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 82 publications
0
4
0
1
Order By: Relevance
“…To the best of our knowledge, this is the first report documenting the role of the neutrophil S1PR2/3 axis in organ transplantation. Others have shown that treatment with FTY720 (fingolimod) targeting S1PR1 prevented T cell egress from lymph nodes in cardiac, kidney, and hematopoietic cell transplant models ( 37 39 ). In addition, the function of S1PRs may be cell type specific.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report documenting the role of the neutrophil S1PR2/3 axis in organ transplantation. Others have shown that treatment with FTY720 (fingolimod) targeting S1PR1 prevented T cell egress from lymph nodes in cardiac, kidney, and hematopoietic cell transplant models ( 37 39 ). In addition, the function of S1PRs may be cell type specific.…”
Section: Discussionmentioning
confidence: 99%
“…In a human phase II trial, cannabidiol was also able to prevent aGvHD [239]#. The broad S1P 1 agonist, fingolimod, is approved for the treatment of multiple sclerosis and works by sequestering lymphocytes in secondary lymphoid organs [240]#. A more specific agonist (CYM-5442) was shown to reduce the severity of murine aGvHD by inhibiting macrophage recruitment via a reduction of CCL2 and CCL7 expression on endothelial cells [241].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous chemical and natural compounds have been identified for their potential to enhance the migratory capabilities of cells while maintaining their regenerative potential and differentiation capacity [ 40 , 86 ]. Chemical compounds like sphingosine-1-phosphate (S1P) and stromal cell-derived factor-1 (SDF-1) have shown promise in promoting cell migration by activating specific signaling pathways involved in cell movement, such as the PI3K/Akt and MAPK pathways [ 87 ]. Additionally, natural compounds such as epigallocatechin-3-gallate (EGCG) found in green tea and curcumin derived from turmeric have demonstrated the ability to modulate cell migration through their anti-inflammatory and antioxidant properties without compromising stem cell identity [ 88 ].…”
Section: Discussionmentioning
confidence: 99%